(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The subject Performative Practices in Dialogue with Eastern Approaches: Perception, Senses, and Imagination was offered over three semesters in the Department of Performing Arts at the University of Brasília (UnB). The text reflects on the methods adopted in the creative processes, organized into three cycles: flower, water, and moon. The methodology incorporated Eastern and somatic body practices, technology, improvisation, dream narratives, nature walks, tarot readings, haiku creation, collages, and watercolors, all aimed at exploring performative approaches and opening spaces for sensory fields. Performances, video performances, an Instagram profile, two art journals, and the Body Haiku e-book were created.